Triploporella ? edgelli n. sp., a new Dasycladalean alga from the Lower Cretaceous of Lebanon - Sibelle Maksoud; Bruno Granier; Dany Azar (Island Arc, 2017)
The Dasycladalean assemblage of the Jezzinian strata (uppermost Barremian–lowermost Aptian) of Lebanon consists of two organo‐genera and eight genera with eleven species, including eight Triploporellaceae. Although Triploporella marsicana (Praturlon, 1964) was reported by Saint‐Marc from the same interval, it is not found in our material. However, a lookalike, which is herein described as Triploporella ? edgelli n. sp., is identified. This new species has cyst‐containers within the primary segments of its laterals but, because it lacks calcified secondary segments, it is left in open nomenclature.